Distribution, Biology and Damage Potential of Suidasia nesbitti Hughes in Stored Grains - Poonam Devi; Rachna Gulati (Research Highlights in Agricultural Sciences Vol. 1, 2022)
Suidasia nesbitti is a stored grain pest that feeds on proteins, carbs, fats, and vitamins, with a preference for high protein and fat content. Asia, Africa, Australia, Europe, North America, the West Indies, and the United Kingdom have all reported it. It feeds on a variety of compounds found in grains, flour, straw, hay, brewer’s yeast, cheese, dried fish and fruit. They favour flour and broken form because it provides more surface area for the S. nesbitti population to flourish on. Under adverse conditions, mite undergo non feeding stage, deutonymph, also known as hypopus between protonymph and tritonymph. Mite infestation reduces protein, total soluble sugar, non-reducing sugar, and starch content while increasing reducing sugar content. Infestation of S. nesbitti causes germination losses in stored products due to its feeding on germinal portion of the grains. The purpose of this review is to collect all existing information on S. nesbitti, including its occurrence, food component preferences, biology, and function in generating post-harvest losses, and to present it systematically under various subheads.